Biologic medicine inclusion in 138 national essential medicines lists - Raphaël Kraus; Rae S. M. Yeung; Nav Persaud (BMC, 2021)
Abstract Background Essential medicines lists (EMLs) are intended to reflect the priority health care needs of populations. We hypothesized that biologic disease-modifying antirheumatic drugs (DMARDs) are underrepresented relative to conventional DMARDs in existing national EMLs. We aimed to survey the extent to which biologic DMARDs are included in EMLs, to determine country characteristics contributing to their inclusion or absence, and to contrast this with conventional DMARD therapies. Methods We searched 138 national EMLs for 10 conventional and 14 biologic DMARDs used in the treatment of childhood rheumatologic diseases. Via regression modelling, we determined country characteristics accounting for differences in medicine inclusion between national EMLs. Results Eleven countries (7.97%) included all 10 conventional DMARDs, 115 (83.33%) ≥5, and all countries listed at least one. Gross domestic product (GDP) per capita was associated with the total number of conventional DMARDs included (β11.02 [95% CI 0.39, 1.66]; P = 0.00279). Among biologic DMARDs, 3 countries (2.2%) listed ≥10, 15 (10.9%) listed ≥5, and 47 (34.1%) listed at least one. Ninety-one (65.9%) of countries listed no biologic DMARDs. European region (β1 1.30 [95% CI 0.08, 2.52]; P = 0.0367), life expectancy (β1-0.70 [95% CI -1.22, − 0.18]; P = 0.0085), health expenditure per capita (β1 1.83 [95% CI 1.24, 2.42]; P < 0.001), and conventional DMARDs listed (β1 0.70 [95% CI 0.33, 1.07]; P < 0.001) were associated with the total number of biologic DMARDs included. Conclusion Biologic DMARDs are excluded from most national EMLs. By comparison, conventional DMARDs are widely included. Countries with higher health spending and longer life expectancy are more likely to list biologics.